The Effect of Ristorante's Rebranding on Pizza Hut Customer Loyalty After the Boycott in Greater Jakarta - Aldi Akbar Ramadhan; Ismail Yusuf; Nizza Nadya Rachmani (The Future of Education Journal, 2025)
This study is motivated by changes in consumer behavior following the boycott issue against several international brands, including Pizza Hut Indonesia, which has affected customer loyalty. In response to this situation, Pizza Hut introduced a new concept called Ristorante in the Jabodetabek area. This research tends to examine the influence of the Ristorante rebranding on customer loyalty after the boycott. The study applied a quantitative method with a descriptive and verificative approach. The participants contained of one hundred and fifty respondents choosed through purposive sampling. Data were collected using a Likert-scale questionnaire with five levels of responses and examined using a simple linear regression method. The findings revealed that the rebranding variable obtained an average score categorized as high, while the customer loyalty variable was also classified as high. The regression analysis indicated that rebranding had a positive and significant influence on customer loyalty. This result suggests that the better the implementation of the Ristorante rebranding strategy by Pizza Hut, the greater the level of customer loyalty established after the boycott. These findings confirm that a well-executed rebranding strategy can serve as an effective means to rebuild consumer trust and strengthen brand loyalty during a reputational crisis.